ChemInform Abstract: Correlating Structure and Function of Metal Nanoparticles for Catalysis. Issue 40 (October 2015) - Zhang, Liang; Anderson, Rachel M.; Crooks, Richard M.; Henkelman, Graeme
Abstract Review: 48 refs.